SOBAT SADEAN Sebagai Inovasi Mahasiswa dalam Menyajikan Kopi Berkualitas dan Membangun Brand Berkelanjutan - Ahmad Nadhim M; M. Salva Putra E; Fikri Ramadhani A; Anang Ihza P; Ilham A; Abdimas Arga (Jurnal Visi Manajemen, 2024)
SOBAT SADEAN is a student entrepreneurship initiative that focuses on serving high-quality coffee with an innovative and sustainable approach. Palm sugar coffee is a superior product that combines traditional and modern flavors, aimed at answering market needs for quality drinks that suit the tastes of the younger generation. Through a digital marketing system and offline promotion, this business shows the potential to compete in the local coffee market. This study discusses the background, business overview, and results and evaluation of the implementation of the SOBAT SADEAN business for three months. Based on the results, this business has succeeded in creating a unique experience for consumers and building a brand that is relevant to market needs.